International Conference on Networking, International Conference on Systems and International Conference on Mobile Communicatio
DOI: 10.1109/icniconsmcl.2006.196
|View full text |Cite
|
Sign up to set email alerts
|

SIRENA - Service Infrastructure for Real-time Embedded Networked Devices: A service oriented framework for different domains

Abstract: The SIRENA project started in 2003 to leverage Service Oriented Architectures (SOA) to seamlessly interconnect (embedded) devices inside and between four distinct domains -the industrial, telecommunication, automotive and home automation domain. A framework was developed to achieve this aim as well as assuring interoperability with existing devices and extensibility of network based on SIRENA technology. The core of the framework is the Devices Profile for Web Services (DPWS) which will play an important role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
1

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(65 citation statements)
references
References 7 publications
0
64
0
1
Order By: Relevance
“…The middleware simplifies the management of underlying devices or things for enterprise application especially in the industrial automation. It is an extension of two previous work projects [29,30].…”
Section: Related Workmentioning
confidence: 98%
“…The middleware simplifies the management of underlying devices or things for enterprise application especially in the industrial automation. It is an extension of two previous work projects [29,30].…”
Section: Related Workmentioning
confidence: 98%
“…Advantages and disadvantages of the aforementioned service technologies applied to different applications are already being studied by researchers (e.g. [5]); thus, a comparison of them is not included in this paper. The analysis performed in research projects such as SIRENA, SOCRADES and within the research program ITEA gives priority to SOAP-based web services in which the devices are integrated with the IT systems using DPWS.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Moreover, research analysis has shown its applicability for embedded systems development [4]. The prototype systems implemented within the European project SIRENA [5] as well as some commercial products that provide support for Devices Profile for Web Services standard [6] further prove the applicability of the SOA concept in the embedded domain. However, applying SOA to deeply constrained devices such as sensor nodes is still an open research problem due to unacceptable overhead.…”
Section: Introductionmentioning
confidence: 99%
“…home automation devices are featured by sparse resources and low processing power and solutions as web services are unsatisfactory because they put high demands on the embedded devices [27]. Other approaches have been driven to service-oriented infrastructures based on the Device Profile for Web Services (WS-DP or DPWS) [28]. DPWS favours the adoption of the SOA paradigm in the embedded-device supporting the integration of deviceprovided services in enterprise-wide application scenarios.…”
Section: Background and Related Workmentioning
confidence: 99%